(untitled) (Zaporizhzhia Historical Review, 2021)
Protestants occupy a certain cell in the religious surrounding of Ukraine and they are representatives of the religious directions which are traditional for Ukraine. The relations between the traditional churches and Protestant communities can be defined as strained ones. Today Protestants have made a choice in favour of special activity. They make a wide spectrum of mercy tasks.